Quality of life of patients with facial prosthesis - Douglas Rangel-Goulart; Eder Alberto Sigua-Rodriguez; Natalia Alvarez-Pinzón; Aline Úrsula Rocha-Fernandes; Elizabeth Queiroz (Universidad de Antioquia, 2017)
Objective: evaluate the quality of life and self-esteem of patients with facial deformities in the nasal, oculo-palpebral, and auricular areas using bucco-maxillofacial prostheses. Methods: descriptive study in users of facial prostheses who were rehabilitated at the dental clinic of the University Hospital of Brasilia in the period 2004-2011. The average age of patients was 63.8 years. The data collection instruments were the SF-36 questionnaire and a survey containing the Rosenberg Self-Esteem/EPM scale. Results: skin cancer was the predominant etiologic factor (n = 4). Most patients think that their deformity is visible to some degree (n = 4) and for three of them this fact impacts negatively the frequency to visit public places. The self-esteem scale yielded an average score of 4.6. In evaluating the quality of life by means of the SF-36 questionnaire, there were scores like pain (46.67) and emotional aspects (33.33). Conclusion: the results demonstrate the importance of conducting systematic follow-ups to these patients. Most surveyed patients experienced an increase in quality of life, as well as a higher self-esteem, which can be explained by the functionality and aesthetics offered by the prosthesis. This study is part of an assessment program conducted with the intention of structuring multidisciplinary rehabilitation programs.